Rilpivirine plus cobicistat-boosted darunavir as a two-drug switch regimen in HIV-infected, virologically suppressed subjects on steady standard three-drug therapy: a randomized, controlled, non-inferiority trial (PROBE 2). (4th March 2020) - Maggiolo, F; Gianotti, N; Comi, L; Di Filippo, E; Fumagalli, L; Nozza, S; Galli, L; Valenti, D; Rizzi, M; Castagna, A
Abstract: Background: We explored the combination of rilpivirine plus cobicistat-boosted darunavir [a two-drug regimen (2DR)] when switching from standard triple combined ART. Methods: In this randomized, open-label, non-inferiority trial, participants had an HIV-RNA <50 copies/mL on a stable (>6 months) three-drug regimen. The primary endpoint was proportion with HIV-RNA <50 copies/mL at Week 24 (snapshot algorithm), with a –12% non-inferiority margin. ClinicalTrials.gov: NCT04064632. Results: One hundred and sixty patients were allocated (1:1) to 2DR or to continue current ART (CAR). At Week 24, 72 (90.0%) of participants with 2DR and 75 (93.8%) with CAR maintained HIV-RNA <50 copies/mL [difference −3.75% (95% CI = −11.63 to 5.63)], confirming non-inferiority. Non-inferiority was confirmed considering an HIV-RNA >50 copies/mL (0% for 2DR; 3.7% for CAR; 95% CI = −0.4 to 7.9). Four patients reported adverse events not leading to treatment discontinuation (one patient in the 2DR group and three patients in the CAR group); eight subjects discontinued therapy in the 2DR group and three in the CAR group. With 2DR, lipid serum concentrations increased, but differences were statistically significant only for tenofovir disoproxil fumarate-containing CAR and in 2DR patients receiving a pre-switch regimen including tenofovir disoproxil fumarate. Median bone stiffness decreased in the CAR group from 86.1 g/cm 2 (IQR = 74–98) to 83.2 g/cm 2 (IQR = 74–97) and increased in the 2DR group from 84.9 g/cm 2 (IQR = 74–103) to 85.5 g/cm 2 (IQR = 74–101). The reduction within the CAR group was significant ( P = 0.043). Conclusions: Once-daily rilpivirine plus cobicistat-boosted darunavir is an effective 2DR that combines a high virological efficacy with a potential to avoid major NRTI toxicities.